2022
DOI: 10.37201/req/066.2022
|View full text |Cite
|
Sign up to set email alerts
|

Unresolved issues in the epidemiology and diagnosis of bacteremia: an opinion paper

Abstract: Bacteremia is an important cause of morbidity and mortality worldwide and, despite the diagnostic and therapeutic advances of the last decades, the evidence supporting many diagnostic aspects of bacteremia is scarce. Information on the epidemiological evolution of this entity is limited and many methodological aspects of blood culture collection and analysis are under discussion. Furthermore, the recommendations of the main scientific societies on many of these aspects are variable and, in many cases, have not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 171 publications
0
4
0
2
Order By: Relevance
“…Indications for blood cultures in human medicine are similar to those in equine medicine, with blood cultures most often collected from neonates and adults with fever/SIRS of unknown origin and/or localised infection with suspected related bacteraemia, with a wide variety of protocols described in the literature. [41][42][43][44][45][46][47] In general, blood cultures in infants are collected from a single site at the time of IV catheter placement, with a goal of 1-2 ml blood per blood culture vial, while in adults, a larger volume of 5-20 ml is collected from one or more venipuncture sites for culture. 14,45 3 | OPTIMISATION OF BLOOD CULTURE YIELD AND ACCURACY…”
Section: Humansmentioning
confidence: 99%
“…Indications for blood cultures in human medicine are similar to those in equine medicine, with blood cultures most often collected from neonates and adults with fever/SIRS of unknown origin and/or localised infection with suspected related bacteraemia, with a wide variety of protocols described in the literature. [41][42][43][44][45][46][47] In general, blood cultures in infants are collected from a single site at the time of IV catheter placement, with a goal of 1-2 ml blood per blood culture vial, while in adults, a larger volume of 5-20 ml is collected from one or more venipuncture sites for culture. 14,45 3 | OPTIMISATION OF BLOOD CULTURE YIELD AND ACCURACY…”
Section: Humansmentioning
confidence: 99%
“…Studies in adults have demonstrated that taking multiple BCs increases pathogen isolation, with the first BC set detecting approximately 75% of pathogens, the second set adding 15-20%, and the third set adding about 7% [9,10]. Guidelines recommend obtaining 2-4 BC sets from different venipunctures per blood culturing episode [11,12], and advise against taking a single set because of its low sensitivity and potential difficulties in the interpretation of results [13].…”
Section: Introductionmentioning
confidence: 99%
“…La identificación temprana de las bacteriemias es un reto importante para el personal médico, ya que es considerada un problema clínico y de salud pública a nivel mundial, no solo como entidad patológica propia sino por las diversas complicaciones infecciosas y no infecciosas que esta produce, siendo responsable de tasas elevadas de morbimortalidad (1,2) . La tasa actual de mortalidad mundial por bacteriemia varia de 21 a 32 muertes por 100 000 habitantes (3) , dato que refleja la importancia de su detección, basándose en la identificación de bacterias viables en el torrente sanguíneo del paciente, lo que se logra mediante la realización de hemocultivos (4) .…”
Section: Introductionunclassified